Digital vs. conventional implant impressions: efficiency outcomes. Issue 1 (22nd February 2012) - Lee, Sang J.; Gallucci, German O.
Abstract: Objectives: The aim of this pilot study was to evaluate the efficiency, difficulty and operator's preference of a digital impression compared with a conventional impression for single implant restorations. Materials and methods: Thirty HSDM second year dental students performed conventional and digital implant impressions on a customized model presenting a single implant. The outcome of the impressions was evaluated under an acceptance criteria and the need for retake/rescan was decided. The efficiency of both impression techniques was evaluated by measuring the preparation, working, and retake/scan time (m/s) and the number of retakes/rescans. Participants' perception on the level of difficulty for the both impressions was assessed with a visual analogue scale (VAS) questionnaire. Multiple questionnaires were obtained to assess the participants' perception on preference, effectiveness and proficiency. Results: Mean total treatment time was of 24:42 m/s for conventional and 12:29 m/s for digital impressions ( P  <   0.001). Mean preparation time was of 4:42 m/s for conventional and 3:35 m/s for digital impressions ( P  <   0.001). Mean working time including retakes/rescans demanded 20:00 m/s for conventional vs. 8:54 m/s for digital impression ( P  <   0.001). On a 0–100 VAS scale, the participants scored a mean difficulty level of 43.12 (±18.46) for conventional impression technique and 30.63 (±17.57) for digital impression technique ( P  = 0.006). Sixty percent of the participants preferred the digital impression, 7% the conventional impression technique and 33% preferred either technique. Conclusions: Digital impressions resulted in a more efficient technique than conventional impressions. Longer preparation, working, and retake time were consumed to complete an acceptable conventional impression. Difficulty was lower for the digital impression compared with the conventional ones when performed by inexperienced second year dental students.